2005
DOI: 10.1111/j.0105-1873.2005.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Hapten–protein binding: from theory to practical application in the in vitro prediction of skin sensitization

Abstract: In view of the forthcoming European Union ban on in vivo testing of cosmetic and toiletry ingredients, following the publication of the 7th amendment to the Cosmetics Directive, the search for practical, alternative, non-animal approaches is gathering pace. For the end-point of skin sensitization, the ultimate goal, i.e. the development and validation of alternative in vitro/in silico assays by 2013, may be achieved through a better understanding of the skin sensitization process on the cellular and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 71 publications
4
142
0
4
Order By: Relevance
“…Subsequently, researchers in the field of contact allergy have shown that the reactivity of a chemical and its ability to bind covalently to protein is indisputably linked to the activation of immune cells and sensitizing potential (Meschkat et al, 2001a,b;Alvarez-Sanchez et al, 2003). In fact, these observations have resulted in the development and use of chemical reactivity measurements for the predictive identification of skin sensitizing chemicals (Divkovic et al, 2005;Gerberick et al, 2007Gerberick et al, , 2008. The development of sophisticated protein mass spectrometry methods to measure the binding of sensitizing chemicals to protein has greatly assisted analysis of chemical protein interactions (Jenkins et al, 2008).…”
Section: The Antigenicity and Immunogenicity Of Directly Reactive mentioning
confidence: 99%
“…Subsequently, researchers in the field of contact allergy have shown that the reactivity of a chemical and its ability to bind covalently to protein is indisputably linked to the activation of immune cells and sensitizing potential (Meschkat et al, 2001a,b;Alvarez-Sanchez et al, 2003). In fact, these observations have resulted in the development and use of chemical reactivity measurements for the predictive identification of skin sensitizing chemicals (Divkovic et al, 2005;Gerberick et al, 2007Gerberick et al, , 2008. The development of sophisticated protein mass spectrometry methods to measure the binding of sensitizing chemicals to protein has greatly assisted analysis of chemical protein interactions (Jenkins et al, 2008).…”
Section: The Antigenicity and Immunogenicity Of Directly Reactive mentioning
confidence: 99%
“…Reactive amino acid residues that play a role in skin sensitization include cysteines (thiol), lysines (amino) and to a lesser extent arginines, histidines, methionines and tyrosines. 45 It has been previously demonstrated that the epoxy reactive diluent PGE reacts selectively with the thiol residue of a model peptide. 23 We firstly investigated the reactivity of DGEBF and compound 2 with a cysteine derivative (N-acetyl-L-cysteine methyl ester, N-ACME).…”
Section: Reactivity Towards the Thiol Residue In Cysteine And In A Momentioning
confidence: 99%
“…A European Union ban on in vivo testing of cosmetic and toiletry ingredients will be enforced in 2013, therefore, there is a need to develop novel and accurate alternative methods for assessing hazard risks and potential potencies of sensitizing chemicals (Divkovic et al, 2005). Several contact sensitizers, known to cause hypersensitivity responses, have been shown to directly induce DC maturation in vitro (Arrighi et al, 2001) (Coutant et al, 1999).…”
Section: Introductionmentioning
confidence: 99%